Peningkatan Kapasitas Kader dalam Pendampingan Penderita Tuberkulosis Paru Di Desa Linggasari Kecamatan Kembaran Kabupaten Banyumas - Rejeki, Dwi Sarwani Sri; Rahadjo, Setiyowati; Nurlaela, Sri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
To ensure the regularity of treatment for pulmonary TB patients, Drug Supervisor (PMO) is necessary. One of the villages in the area of Puskesmas Kembaran I which still encountered pulmonary tuberculosis was Linggasari Village. The problems in this village were the increasing number of TB patients and TB cases with drug resistance (TB-RO), irregularity in the treatment and some even stop to have treatment. The factor affecting these situations was the ineffective role of PMO in the family. The cadres in Linggasari Village were posyandu cadres for toddlers and the elderly. To suppress the increasing number of TB and TB-RO cases, cadres could increase its role as PMO. Recently, cadres still obtained limited knowledge and skills on TB disease and its treatment. They were also lack of communication and negotiation skills to convince TB sufferers to get regular treatment. This activity aimed to increase the knowledge and skills of cadres in working as PMO cadres for pulmonary TB disease. To increase the knowledge and skills of cadres as PMO, it was necessary to provide cadres guidance on PMO and other supporting facilities. These activities included 1) Writing cadres’ manuals 2) Health education for cadres 3) Effective communication training for cadres 4) Mentoring, 5) Procurement of supporting facilities. The results of the activities indicated that there was an increase in the knowledge and skills of the cadres before and after the activities. The manual book for cadres is very useful in assisting pulmonary TB sufferers.